A−Summation process in the space of locally integrable functions - ȘAHIN BAYRAM, Nilay; ORHAN, Cihan (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In this paper, using the concept of summation process, we give a Korovkin type approximation theorem for a sequence of positive linear operators acting from Lp,q (loc) , the space of locally integrable functions, into itself. We also study rate of convergence of these operators. Mathematics Subject Classification (2010): 41A25, 41A36.